Growth, yield and quality of turmeric (Curcuma longa L.) as influenced by planting time and fertility levels - M K Pathak, S K Tiwari, J K Tiwari, (Journal of Spices and Aromatic Crops, 2014)
This study was carried out to evaluate the growth, yield and quality of turmeric as influenced by dates of planting and fertility levels. The experiment was laid out in split plot design with four dates of planting (first fortnight of May (D1), second fortnight of May (D2), first fortnight of June (D3) and second fortnight of June (D4) in main plots, four fertility levels (NPK @ 0:0:0 kg ha-1 (F0), NPK @ 125:25:30 kg ha-1 (F1), NPK @ 150:50:60 kg ha-1 (F2) and NPK @ 175:75:90 kg ha-1 (F3) in sub plots and two varieties [Rajendra Haldi-5 (V1) and Rajendra Sonia (V2)] in ultimate plots. Yield attributes i.e. weight of primary, secondary and mother rhizomes, number of primary and secondary rhizomes, fresh rhizome yield clump-1 and yield ha-1 were found to be significantly higher when planted during first fortnight of June. Fertility levels imparted significant effect on plant height, number of tillers clump-1, weight of primary, secondary and mother rhizomes, length of mother rhizome, number of primary and secondary rhizomes, fresh weight of rhizome clump-1 and yield. These parameters were significantly higher in F2. Among the varieties, Rajendra Sonia performed better with regard to plant height, number of tillers clump-1, weight of mother, primary and secondary rhizomes, length of mother rhizomes, number of primary and secondary rhizomes, fresh rhizome weight clump-1 and yield. Among the interactions, Rajendra Sonia supplied with NPK @ 175:75:90 kg ha-1 produced higher yield and was at par with F2V2 (NPK @ 150:50:60 kg ha-1 + Rajendra Sonia).